2017
DOI: 10.1177/1557988317736585
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Low-Intensity Extracorporeal Shock Wave Therapy on Men With Chronic Pelvic Pain Syndrome Refractory to 3-As Therapy

Abstract: Managing patients with chronic pelvic pain syndrome (CPPS) refractory to the traditional 3-As therapy (antibiotics, alpha-blockers, and anti-inflammatories) is a challenging task. Low-intensity extracorporeal shock wave therapy (LI-ESWT) was recently reported to be able to improve pain, urinary symptoms, and even sexual function by inducing neovascularization and anti-inflammation, reducing muscle tone, and influencing nerve impulses. This study evaluates whether combined treatment with LI-ESWT can restore cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 44 publications
1
40
1
2
Order By: Relevance
“…Clinical trials on the safety and efficacy profile of LiESWT in treating female SUI are still not completely clear. Clinically, LiESWT has emerged in recent years to treat (1) chronic pelvic pain syndrome (CPPS) (0.10-0.25 mJ/ mm 2 , 3000 pulses, once/week, 4 weeks) to improve pain, bladder voiding and QoL 17,[24][25][26][27] ; (2) erectile dysfunction (ED) (0.10-0.25 mJ/mm 2 , 3000-6000 pulses, once/week, 4-8 weeks) to increase penile hemodynamics and induce penile tissue regeneration 18,28,29 . In this study, the recruited subjects had normal BMI, blood pressure, renal function, liver function, blood sugar level, and lipid profiles, thus eliminating the potential confounding factors ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials on the safety and efficacy profile of LiESWT in treating female SUI are still not completely clear. Clinically, LiESWT has emerged in recent years to treat (1) chronic pelvic pain syndrome (CPPS) (0.10-0.25 mJ/ mm 2 , 3000 pulses, once/week, 4 weeks) to improve pain, bladder voiding and QoL 17,[24][25][26][27] ; (2) erectile dysfunction (ED) (0.10-0.25 mJ/mm 2 , 3000-6000 pulses, once/week, 4-8 weeks) to increase penile hemodynamics and induce penile tissue regeneration 18,28,29 . In this study, the recruited subjects had normal BMI, blood pressure, renal function, liver function, blood sugar level, and lipid profiles, thus eliminating the potential confounding factors ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…LiESWT has been used clinically for several years in urology, but the efficacy and safety profile of LiESWT in treating OAB are not completely clear. For the CPPS studies, the shock intensity ranging from 0.10 to 0.25 mJ/mm 2 , 3000 impulses, and once/week treatment continuing for 4 weeks were used to treat the disease [ 17 19 ]. The results showed that LiESWT improved the pain score, bladder urination, and QoL without side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group showed that LiESWT can significantly improve the visual analog scale (VAS) pain score and total international prostate symptom scores (IPSS) for men with CPPS refractory to 3-As therapy (antibiotics, alpha-blockers, and anti-inflammatories). The response can last until the 3-month follow-up [ 19 ]. To date, the clinical efficacy of LiESWT on patients with OAB has not previously been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Two latest studies reviewed literature from 2008 to 2018 (Franco et al, 2018; Guu et al, 2018) on the positive results of fESWT in the improvement of CPPS. Four studies with 237 participants reported that fESWT reduced prostatitis symptoms compared to the sham control or no intervention control, measured by NIH-CPSI score at 12 weeks’ follow-up (Pajovic et al, 2016; Vahdatpour et al, 2013; Zeng et al, 2012; Zimmermann et al, 2009).…”
Section: Discussionmentioning
confidence: 99%